Retouching glass plate negatives. What do old manuals say? - Pereira, Catarina Cortes (2018)
This paper aims to present a study of old photographic retouching manuals which is part of a research pro ject on the retouching of gelatin silver glass plate negatives from Portuguese photographic col lec tions from the first half of the twentieth century. Several contemporary authors of var ious nationalities were studied. Differences in approach to retouching have been ex plored in terms of techniques and materials, particularly as the authors addressed issues such as ethics and the legitimacy of photo retouching, as well as the relationship of photography to the other arts.